Malaysian University Students’ English Academic Reading and Writing Ecology: A Preliminary Description - Daron Benjamin Loo (Malaysian English Language Teaching Association (MELTA), 2023)
This study presents a preliminary description of university students’ ecology of academic reading and writing in English. Data was collected through three online discussion forums, where students could post and discuss about their perceptions and experiences in academic reading and writing. Using a grounded approach, data from these online forum posts were thematized. To ensure credibility of students’ responses, the third forum post was used to triangulate data from the first two forums. Findings indicated that the students had specific experiences of reading, through their mention of various academic texts assigned by their lecturers; however, academic writing was found to be rather general, given the lack of specific information and experiences found in students’ responses. Beyond the university, it was found that students may not be reading materials in the English language, and that their reading was of a variety of genres. These findings bring about the assumption that the ecology for reading and writing, especially in the English language, is confined to the educational setting. It is suggested that English language instructors could leverage on materials students encounter outside the university to encourage reading and writing in English.